2009
DOI: 10.1158/1535-7163.mct-08-1038
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor efficacy of IPI-504, a selective heat shock protein 90 inhibitor against human epidermal growth factor receptor 2–positive human xenograft models as a single agent and in combination with trastuzumab or lapatinib

Abstract: IPI-504 is a novel, highly soluble small-molecule inhibitor of heat shock protein 90 (Hsp90), a protein chaperone essential for regulating homeostasis of oncoproteins and cell signaling proteins. Human epidermal growth factor receptor 2 (HER2; ErbB2) oncoprotein, expressed in a subset of metastatic breast cancers, is a Hsp90 client protein. In this study, we investigated the antitumor activity and the mechanism of action of IPI-504 in HER2 + , trastuzumabsensitive and trastuzumab-refractory cell lines in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…Similar results were observed in tumor models bearing the H1047R PI3K activating mutation or low levels of PTEN, known to be clinically confirmed mechanisms of intrinsic trastuzumab resistance (16,17). Furthermore, it has also been recently shown that IPI-504 reduces tumor growth of JIMT-1 xenografts, which are believed to be intrinsically resistant to trastuzumab because of upregulation of the membrane-associated mucin 4 (27). Taken together, these data suggest that IPI-504 treatment can counteract multiple trastuzumab-resistant mechanisms, which may offer a potential clinical path forward for intervention in this setting.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results were observed in tumor models bearing the H1047R PI3K activating mutation or low levels of PTEN, known to be clinically confirmed mechanisms of intrinsic trastuzumab resistance (16,17). Furthermore, it has also been recently shown that IPI-504 reduces tumor growth of JIMT-1 xenografts, which are believed to be intrinsically resistant to trastuzumab because of upregulation of the membrane-associated mucin 4 (27). Taken together, these data suggest that IPI-504 treatment can counteract multiple trastuzumab-resistant mechanisms, which may offer a potential clinical path forward for intervention in this setting.…”
Section: Discussionsupporting
confidence: 73%
“…Both 17-AAG and IPI-504 have shown activity in multiple models of solid (e.g., lung, breast, pancreatic, and melanoma) and hematologic (e.g., chronic myelogenous leukemia and multiple myeloma) cancers (25)(26)(27)(28). In HER2-positive human breast cancer cell lines, IPI-504 potently downregulates HER2 and inhibits cell growth (27). IPI-504 is currently under clinical investigation in a phase I/II trial in combination with docetaxel that is focused on patients with non-small cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Part 1 Clinical Trial Outcomes tant activities associated with HSP90 inhibition is the reversal of resistance to both trastuzumab and hormonal agents [305,306]. Importantly, there is preclinical data indicating that HSP90 inhibitors are synergistic with both trastuzumab [307][308][309] and lapatinib ditosylate [309,310]. Phase I and II clinical studies of first-generation HSP90 inhibitors have been published [311][312][313].…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%
“…Combination of IPI-504 with transtuzumab significantly enhances tumor growth delay. 70 Combination of IPI-504 with lapatinib also enhances tumor growth delay. 70 The provirus integration site for Moloney murine leukemia virus tumor-specific cell surface antigens (PIM-1) is a proto-oncogene that encodes ser/thr kinase with multiple cellular functions.…”
Section: Actions Ofmentioning
confidence: 99%
“…70 Combination of IPI-504 with lapatinib also enhances tumor growth delay. 70 The provirus integration site for Moloney murine leukemia virus tumor-specific cell surface antigens (PIM-1) is a proto-oncogene that encodes ser/thr kinase with multiple cellular functions. Overexpression of PIM-1 has a critical role in the progression of prostatic and hematopoietic malignancies.…”
Section: Actions Ofmentioning
confidence: 99%